2011
DOI: 10.1088/0957-4484/22/50/505102
|View full text |Cite
|
Sign up to set email alerts
|

Minimal-invasive magnetic heating of tumors does not alter intra-tumoral nanoparticle accumulation, allowing for repeated therapy sessions: anin vivostudy in mice

Abstract: Localized magnetic heating treatments (hyperthermia, thermal ablation) using superparamagnetic iron oxide nanoparticles (MNPs) continue to be an active area of cancer research. For generating the appropriate heat to sufficiently target cell destruction, adequate MNP concentrations need to be accumulated into tumors. Furthermore, the knowledge of MNP bio-distribution after application and additionally after heating is significant, firstly because of the possibility of repeated heating treatments if MNPs remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 24 publications
(27 reference statements)
3
37
0
Order By: Relevance
“…The fact that magnetic thermoablation is very effective in terms of inducing apoptosis/necrosis and reducing tumor volumes has been shown previously. 19 Taken together, our results show for the first time the impact of magnetic thermoablative stimuli (2 minutes) to temperatures up to approximately 65°C on the molecular expression pattern of selected proteins in the tumor region 2 hours after heat shock. As previous results have shown, a threshold for thermoablative temperatures for the elimination of tumor cells was found to be 55°C-60°C as cell survival was strongly impaired when more than 50% of total DNA was irreversibly damaged.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The fact that magnetic thermoablation is very effective in terms of inducing apoptosis/necrosis and reducing tumor volumes has been shown previously. 19 Taken together, our results show for the first time the impact of magnetic thermoablative stimuli (2 minutes) to temperatures up to approximately 65°C on the molecular expression pattern of selected proteins in the tumor region 2 hours after heat shock. As previous results have shown, a threshold for thermoablative temperatures for the elimination of tumor cells was found to be 55°C-60°C as cell survival was strongly impaired when more than 50% of total DNA was irreversibly damaged.…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, no delocalization of MNP due to thermoablative treatment could be observed by comparing the X-ray images obtained before and after AMF, and is in accordance with the literature. 19 Although several publications reported that especially smaller MNP (approximately between 20 nm and 100 nm) were preferentially taken up by tumor cells (eg, by endocytosis), the possibility of the used MNP to be taken up by BT474 tumor cells or, at least, be bound to their membrane was verified in previous experiments. [20][21][22] Two hours after the application of thermoablative temperatures in the tumor region, a downregulation of BCL2 and FGF-R1 was found whereas HSP70 remained unchanged.…”
Section: Discussionmentioning
confidence: 95%
“…[70][71][72][73][74] In later clinical applications, applied MNP will stay at the site of injection up to weeks, allowing the generation of drug depots for a prolonged and/or repeated tumor treatment. 75 By this, the utilization of MTX-MNP as a combinatory therapy is capable of achieving higher cytotoxic results in later clinical applications, with less systemic side effects than systemically applied free MTX.…”
mentioning
confidence: 99%
“…Additionally, the exposure to an alternating magnetic field and the induction of apoptosis did not affect MNP accumulation. Consequently, localized magnetic heating therapy of tumors might be applied periodically for better therapeutic outcome [19].…”
Section: Mnp Exposure To An Alternating Magnetic Field Does Not Releamentioning
confidence: 99%